Letter: eluxadoline‐associated acute pancreatitis—myth or reality?. Issue 4 (24th July 2018) - Garcia‐Gonzalez, F.; Faghih, M.; Singh, V.
Abstract : Linked Content This article is linked to Harinstein et al papers. To view these articles visithttps://doi.org/10.1111/apt.14504 andhttps://doi.org/10.1111/apt.14851 .